Dampak Perceived Environmental Knowledge dan Green Product Terhadap Purchase Decision Melalui Green Awareness: Studi pada Pengguna Produk the Body Shop di Kota Jepara - Lailii Shofiyaa; Nurul Komaryatin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study was to determine the effect of perceived environmental knowledge and green products on purchase decisions through green awareness. The data source used in this study was the distribution of questionnaires to users of The Body Shop products in Jepara as many as 160 respondents. The sampling technique was based on purposive sampling technique where samples were taken from members of the population using specified criteria. The data analysis used was sem-partial least square (pls). The results of the analysis stated that there was a significant influence of the variables perceived environmental knowledge, green products, green awareness on purchase decisions